Structural, electrical and electrochemical characterizations of SrNb0.1Co0.9O3-d as a cathode of solid oxide fuel cells operating below 600 C - Zhou, W.; Jin, W.; Zhu, Z.; Shao, Zongping (Elsevier Ltd, 2010)
SrNb0.1Co0.9O3-d (SNC) perovskite oxide has been prepared by high-energy ball milling followed by calcination at 1100 °C. According to oxygen temperature-programmed desorption and thermogravimetry analysis results, highly charged Nb5+ successfully stabilizes the perovskite structure to avoid order-disorder phase transition. The electrical conductivity reaches 550 S cm-1 at 300 °C in air and as high as 106 S cm-1 under P(O2) = 1 × 10-5 atm at 900 °C. The high electrical conductivity is beneficial in improving the charge-transfer process for the oxygen reduction reaction on the cathode. Based on the defect chemical analysis, the Nb-doping in SrCoO3-d perovskite facilitates the formation of Co2+, which increases oxygen nonstoichiometry and, subsequently, the mixed valence of [Co2+]/[Co3+] under lower oxygen partial pressure. A relatively low thermal expansion coefficient of 19.1 × 10-6 K-1 in air was achieved. All above properties show SNC to be a promising cathode material in the practical application of low-temperature solid oxide fuel cells. © 2009 Professor T. Nejat Veziroglu.